Physical Activity, Guideline Compliance, and Exercise Preferences in Axial Spondyloarthritis: A Comparative Cross-Sectional Study - Serpil Demirulus; Gamze Kilic; Murat Karkucak; Erhan Capkin (Journal of Clinical Medicine, 2026)
Background: Exercise is a cornerstone of axial spondyloarthritis (axSpA) management, yet real-world adherence to physical activity (PA) recommendations and patient preferences for exercise delivery remain insufficiently characterized. This study aimed to compare PA levels, World Health Organization (WHO) aerobic PA guideline compliance, and exercise preferences between patients with axSpA and age and sex-matched healthy controls. Methods: A total of 153 patients with axSpA and 153 age- and sex-matched healthy controls were recruited from a tertiary rheumatology clinic. PA was assessed using the International Physical Activity Questionnaire-Short Form. Compliance with WHO aerobic PA recommendations was defined as achieving ≥150 min/week of moderate-intensity PA including walking, ≥75 min/week of vigorous-intensity PA, or an equivalent combination. Disease activity, function, quality of life, kinesiophobia, fibromyalgia, neuropathic pain, psychological status, and exercise preferences (adapted from the Personalized Exercise Questionnaire) were also recorded, and logistic regression identified factors associated with compliance among axSpA patients. Results: Total IPAQ-SF MET-min/week scores were comparable between groups, but vigorous-intensity activity was lower in axSpA (p = 0.012). Fewer patients with axSpA met WHO aerobic PA recommendations than controls (60.1% vs. 71.2%, p = 0.041) and this gap was most evident among women (43.4% vs. 75.5%, p = 0.002) but not among men, with a significant axSpA status × sex interaction (p = 0.008). Among patients with axSpA, female sex and higher kinesiophobia scores were independently associated with lower odds of meeting the WHO aerobic PA recommendations. Patients with axSpA also showed distinct exercise preferences including greater preference for health-professional supervision, home-based exercise, and regular feedback. Conclusions: Patients with axSpA had lower adherence to WHO aerobic PA recommendations than healthy controls. Among patients with axSpA, female sex and higher kinesiophobia were associated with lower adherence. These findings highlight the importance of considering sex-related differences, kinesiophobia, and individual exercise preferences when developing personalized strategies to promote PA in axSpA.